Catalysis by Metals on Perovskite-Type Oxides - Ferri, Davide (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The acceptance and preference of the sensory properties of foods are among the most important criteria determining food choice. Sensory perception and our response to food products, and finally food choice itself, are affected by a myriad of intrinsic and extrinsic factors. The pressing question is, how do these factors specifically affect our acceptance and preference for foods, both in and of themselves, and in combination in various contexts, both fundamental and applied? In addition, which factors overall play the largest role in how we perceive and behave towards food in daily life? Finally, how can these factors be utilized to affect our preferences and final acceptance of real food and food products from industrial production and beyond for healthier eating? A closer look at trends in research showcasing the influence that these factors and our senses have on our perception and affective response to food products and our food choices is timely. Thus, in this Special Issue collection "Consumer Preferences and Acceptance of Food Products", we bring together articles which encompass the wide scope of multidisciplinary research in the space related to the determination of key factors involved linked to fundamental interactions, cross-modal effects in different contexts and eating scenarios, as well as studies that utilize unique study design approaches and methodologies.